2012
DOI: 10.1103/physrevb.86.075119
|View full text |Cite
|
Sign up to set email alerts
|

Percolation transition in quantum Ising and rotor models with sub-Ohmic dissipation

Abstract: We investigate the influence of sub-Ohmic dissipation on randomly diluted quantum Ising and rotor models. The dissipation causes the quantum dynamics of sufficiently large percolation clusters to freeze completely. As a result, the zero-temperature quantum phase transition across the lattice percolation threshold separates an unusual super-paramagnetic cluster phase from an inhomogeneous ferromagnetic phase. We determine the lowtemperature thermodynamic behavior in both phases, which is dominated by large froz… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Year Published

2017
2017
2018
2018

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 42 publications
0
2
0
Order By: Relevance
“…While at low enough temperatures thermal fluctuations are indeed weak, quantum fluctuations remain present. However, previous studies of diluted quantum magnetic systems found that the percolation threshold and certain percolation critical exponents (such as β and ν) are unaffected by quantum fluctuations [35,36], even in the presence of dissipation [37,38], which is expected to occur on the metallic side of the transition. Finally, we have focused on electrostatic gating, our conclusions also apply to electrochemical doping describing, for example, the transfer of oxygen vacancies into the surface of a sample.…”
mentioning
confidence: 99%
“…While at low enough temperatures thermal fluctuations are indeed weak, quantum fluctuations remain present. However, previous studies of diluted quantum magnetic systems found that the percolation threshold and certain percolation critical exponents (such as β and ν) are unaffected by quantum fluctuations [35,36], even in the presence of dissipation [37,38], which is expected to occur on the metallic side of the transition. Finally, we have focused on electrostatic gating, our conclusions also apply to electrochemical doping describing, for example, the transfer of oxygen vacancies into the surface of a sample.…”
mentioning
confidence: 99%
“…As we show here, the rare regions completely change the nature of the simultaneous first-order nematic-DW quantum transition in a two-dimensional itinerant system. This is because of the crucial role of the droplet's dissipative quantum dynamics [35][36][37], which allows longrange Ising-nematic order in finite-size droplets at T = 0 (see also Ref. [18]), but not long-range DW order (for spin or incommensurate charge density-waves).…”
mentioning
confidence: 99%